The Influence of Self-Control on Aggressiveness in Adolescents: A Systematic Review - Yusfia Hadisty Yusfia; Dhiya Fauziyyah Sudirman; Nimatuzahroh Nimatuzahroh (Research Psychologie, Orientation et Conseil, 2024)
Aggressiveness is the tendency to behave harshly, violently, or hostilely towards others. It can be physical, verbal, or even emotional. Aggressiveness is often considered a negative trait because it can lead to conflicts and harm both oneself and others. One of the factors that can influence it is self-control, which is the ability to restrain or manage impulsive or excessive urges and behaviors. Eight out of 15 international journals indicate that adolescent aggressive behavior includes various types, such as physical aggression, verbal aggression, and modeling aggression. Self-control has a significant influence on adolescent aggressiveness. The results of the systematic review show that good self-control can help manage and direct aggressiveness toward more positive and constructive outcomes. Other factors that influence aggressiveness include gender, parenting styles, and emotional regulation. Therefore, understanding the interaction of these factors is crucial in addressing and managing aggressiveness to foster healthier social interactions and personal well-being.